UWB bandpass filter using coplanar waveguide multiple-mode resonator - Sun, XiaoFeng. (2009)
The main objective of this project is to design and simulate UWB filters using coplanar waveguide (CPW) multiple-mode resonator (MMR). The CPW MMR is formed by loading three short-ended stubs in series. The CPW MMR is made of three sections with high-impedance in middle and low-impedance in two sides. Modified UWM band-pass filter with the microstrip patch was then investigated. By properly adjusting the lengths as well as the widths of patch, the frequency range of this filter covers the UWB frequency range. Introducing a slot in the microstrip patch, a band-notched UWN filter is designed with the narrow stop-band at 5.6 GHz to reject wireless local-area network (WLAN) radio signal.